THE EFFECT OF RED DRAGON FRUIT EXTRACT (RDFE) TOPICALLY ON ACUTE INJURY ON THE CHANGE OF MATRIX METALLOPROTEINASE-9 (MMP-9) AND WOUNDS DIAMETER : AN ANIMAL MODEL STUDY - Masud, Alfian - (ETN Centre Indonesia, 2018)
The wound healing process is complex and is influenced by multifactors, one of which is MMP-9. Dragon fruit is a fruit that became popular because of its healing effect on wounds due to its flavonoid content. However, related research is still limited. This study aims to prove the effect of topical Red Dragon Fruit Extract (RDFE) on changes in MMP-9 levels on acute wistar healing. Researchers used experimental research design with post test with control group design. Animals tried in the form of male wistar (n = 58) with acute injection using 5 mm punch biopsy, divided into 3 groups (control, establish and topical RDFE 7.5%). Measurement of MMP-9 levels with ELISA techniques using wound tissue. Data were analyzed using SPSS 22 with One Way ANOVA Test. The MMP-9 levels in the EBNM group had the lowest levels on day 3 (controls: 1.64 ± 0.82, establish: 1.05 ± 1.09 and RDFE: 0.99 ± 0.95). After 7 days the treatment has approximately the same level (Establish: 1.28 ± 0.61 and RDFE: 1.57 ± 0.72) After 14 days, RDFE has the lowest MMP-9 levels Topical RDFE can decrease MMP-9 levels in all wound healing phases and there is a reduction in wound diameter and no more inferior than establish and control.